SERVICE QUALITY LEARNING AND CUSTOMER RETENTION IN MSMEs: A DYNAMIC CAPABILITY APPROACH - Nazhira Nindya Padma Hanuun; Arief Budiman (Organisasi Kreatif Indonesia Emas, 2025)
This conceptual paper develops an integrative framework for service quality learning and customer retention in micro, small, and medium enterprises (MSMEs). It synthesizes established literature on the resource-based view, dynamic capabilities, organizational learning, absorptive capacity, social capital, resilience, and entrepreneurial ecosystems. The analysis explains how customer feedback, service recovery, process learning, trust formation, and continuous adaptation can be organized into proportionate managerial routines. No primary survey, interview, experimental, or statistical data are claimed. The framework proposes diagnosis, capability mapping, bounded experimentation, evidence review, governance, resource reconfiguration, and learning retention as a cumulative cycle.